1999
DOI: 10.1191/026921699675854885
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patient and proxy symptom assessments in advanced cancer patients

Abstract: The purpose of this study was to compare patient and proxy (physician and nurse) assessments of symptoms in advanced cancer patients. The sample consisted of 49 patients with advanced cancer admitted to an acute palliative care unit. Three independent assessments were completed for each patient on two occasions within 11 days of admission. On each occasion, symptoms were rated independently by the patient and two proxies (treating physician and nurse), using the Edmonton Symptom Assessment System (ESAS). The E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(116 citation statements)
references
References 43 publications
4
108
2
2
Order By: Relevance
“…However, many studies show that proxy ratings of patient's symptoms are not a consistently accurate reflection of patient distress. Nekolaichuk et al [17] demonstrated that whereas nursing staff can often assign symptom scores that are similar to patient scores, Physicians often assign scores that are lower than patients own ratings for their symptoms [18]. In another study, Pautex et al [19] reported that Physician and Nurse Assessments of patient symptom scores were similar; however both differed from patient ratings.…”
Section: Discussionmentioning
confidence: 93%
“…However, many studies show that proxy ratings of patient's symptoms are not a consistently accurate reflection of patient distress. Nekolaichuk et al [17] demonstrated that whereas nursing staff can often assign symptom scores that are similar to patient scores, Physicians often assign scores that are lower than patients own ratings for their symptoms [18]. In another study, Pautex et al [19] reported that Physician and Nurse Assessments of patient symptom scores were similar; however both differed from patient ratings.…”
Section: Discussionmentioning
confidence: 93%
“…Lower correlations were apparent for subjective items of anxiety, depression, and well-being. Correlation coefficients for physician-or-patient ratings were weakest for activity (0.33), depression (0.45), and well-being (0.44) 20 ; for nurse-or-patient ratings, coefficients were weaker overall, with 0.35 for activity, 0.37 for depression, and 0.23 for well-being. Interestingly, proxy scores did not converge with patient self-scores over 2 weeks of follow-up.…”
Section: Reliabilitymentioning
confidence: 99%
“…More than 130 relevant articles and abstracts were identified, of which thirty-nine were primary studies published as complete peer-reviewed papers, representing 25 different institutions. Of the thirty-nine papers, thirteen were from Canada 6,11,[20][21][22][23][24][25][26][27][28][29][30] ; eight were from the United States [12][13][14]18,[31][32][33][34] ; eight were from Scandinavia (Sweden 15,[35][36][37] , Denmark [38][39] , Norway 40 , Finland 16 ); two were from Western Europe (Netherlands 41 , United Kingdom 42 ); five were from southern Europe (Switzerland 43 , Italy 17,[44][45][46] ); two were from Australia 47,48 ; and one was from Asia 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Proxy interviews are administered to caregivers of individuals nearing end of life, to relieve the respondent burden for those who are terminally ill (8,9). Proxy reports have been shown to be quite accurate for observable symptoms such as vomiting; however, the agreement between self and proxy reporting has been shown to be unreliable for symptoms that are less observable, such as pain or depression (8).…”
Section: Introductionmentioning
confidence: 99%